Healthy Behaviors of Female Teenagers Living in Orphanage Centers and Living with their Families - N Nejat; Z Kashaninia; R Memarian (Tehran University of Medical Sciences, 2008)
Background & Aim: Healthy behaviors of teenagers are effective on the community development. This study was carried out in order to compare healthy behaviors of female teenagers living with their families and in orphanage centers in Tehran. Methods & Materials: This was a cross-sectional study. The subjects were consisted of 110 female teenagers that 55 of them dwelled in the orphanage centers and the remaining lived with their families. Both groups were studying at the same schools. Samples were selected using stratified random sampling method. Questionnaire was used to gather data. The data were analyzed by descriptive and analytical statistical methods in SPSS software. Results: There were statistically significant differences between two groups in nutrition (P<0.0003), sleep & rest (P<0.001), physical exercise (P<0.0013), and individual health (P<0.001). Total score of health behaviors were 112.3, and 87.8 in family group and orphanage group respectively (P<0.001). Conclusion: The average score of health behaviors in girls that reside in orphanage centers was lower than the score of them who lived with their families. This shows the necessity of planning educational and managerial tools to improve their healthy behaviors.